Synthesis of new polyurethaneureas with decametoxine containing fragments of copolymers of N-vinyl pyrrolidone with vinyl alcohol - Karpenko, O. S.; Kiseleva, T. O.; Galatenko, N.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
The article is devoted to the synthesis of new biologically active polyurethaneureas. The new polyurethaneureas with drug – decametoxine containing fragments of a copolymer of N-vinyl pyrrolidone with vinyl alcohol, which can be used in the future as polymers for the treatment of wounds and burns, are synthesized. The IR-spectroscopy research testified that decametoxin is immobilized on a polymer through physical bonds.